Natural photosensitizers for dye sensitized solar cells - Mohamad, Souad A.; Alaei, Iraj; Sopyan, Iis (IJRER, 2013)
Dye-sensitized solar cells (DSSCs) were constructed by using the Lawsonia inermis leaves, Sumac/Rhus fruits, and Curcuma longa roots as natural sensitizers of anatase-based nanostructure TiO2 thin film Paint-coated on ITO conducting glass. The orange-red Lawsone, red purple anthocyanin and yellow Curcumin are the main components in the natural dyes obtained from these natural products. A blend of 50 wt% chitosan and 50 wt% polyethylene oxide (PEO) was used as a solid state thin film electrolyte. The polymer blend was complexed with ammonium iodide (NH4I) and some iodine crystals were added to the polymer–NH4I solution to provide I-/I3- redox couple. The ionic conductivity of the polymer electrolyte is 1.18x10-5 S cm-1 at room temperature. Structural and optical properties of the semiconductor thin films were characterized by X-ray diffractometer and UV-VIS spectrophotometer respectively. The XRD shows nanocrystalline structures for TiO2 thin films (D=13nm). The photovoltaic properties of the cell have been studied and the best overall solar energy conversion efficiency of 1.5% was obtained, under AM 1.5 irradiation, with the red purple Sumac/Rhus extract, that showed a reasonable current density (Jsc = 0.93 mA/cm2).